Penerapan Pembelajaran Kontekstual Berbantuan Hypermedia Interaktif iSpring untuk Meningkatkan Literasi Digital - Abdul Wakhid Mustofa (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to improve students' digital literacy by using a contextual approach with the help of iSpring Interactive Hypermedia. The subjects in this study were fourth grade students at Bukit Indah Singura Remote Elementary School in the 2019/2020 Academic Year. The method used in this study is descriptive qualitative with instruments in the form of questionnaires and observation sheets. The results showed that the basic abilities of digital literacy in the class as a whole were in the high and medium categories with achievements on the ICT usage indicators a percentage of 80%, included in the medium category, students' understanding of information by 88% included in the high category, and the ability to use ICT in learning by 85% with the high category). The average learning outcomes in the knowledge aspect is 80 and all students are able to achieve learning mastery. It can be concluded that students' digital literacy skills increased after participating in learning using a contextual approach with the help of iSpring Interactive Hypermedia.